2016
DOI: 10.1039/c5dt04907e
|View full text |Cite
|
Sign up to set email alerts
|

A non-typical sequence of phase transitions in (NH4)3GeF7: optical and structural characterization

Abstract: Single crystals of germanium double salt (NH4)3GeF7 = (NH4)2GeF6·NH4F = (NH4)3[GeF6]F were grown and studied by the methods of polarization optics and X-ray diffraction. The birefringence Δn = (no - ne), the rotation angle of the optical indicatrix ϕ(T) and unit cell parameters were measured in the temperature range 100-400 K. Three structural phase transitions were found at the temperatures: T1↓ = 279.2 K (T1↑ = 279.4 K), T2↑ = 270 K (T2↓ = 268.9 K), T3↓ = 218 K (T3↑ = 227 K). An unusual sequence of symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 17 publications
8
25
0
Order By: Relevance
“…Calorimetric measurements revealed the succession of four reversible phase transitions below room temperature: T 1 = 263 ± 1 K; T 2 = 198 ± 1 K; T 3 = 194 ± 1 K; T 4 = 170 ± 1 K, and an absence of transformation into the Pm3m phase up to decomposition. It was found that the application of uniaxial pressure does not change the orientation of the four-fold axis of (NH 4 ) 3 SiF 7 , similar to (NH 4 ) 3 GeF 7 , 11 which is in agreement with the fact that they are isostructural at room temperature. Therefore, both (NH 4 ) 3 SiF 7 and (NH 4 ) 3 GeF 7 differ from (NH 4 ) 3 TiF 7 in which the high-pressure parent phase Pm3m is attainable.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Calorimetric measurements revealed the succession of four reversible phase transitions below room temperature: T 1 = 263 ± 1 K; T 2 = 198 ± 1 K; T 3 = 194 ± 1 K; T 4 = 170 ± 1 K, and an absence of transformation into the Pm3m phase up to decomposition. It was found that the application of uniaxial pressure does not change the orientation of the four-fold axis of (NH 4 ) 3 SiF 7 , similar to (NH 4 ) 3 GeF 7 , 11 which is in agreement with the fact that they are isostructural at room temperature. Therefore, both (NH 4 ) 3 SiF 7 and (NH 4 ) 3 GeF 7 differ from (NH 4 ) 3 TiF 7 in which the high-pressure parent phase Pm3m is attainable.…”
Section: Discussionsupporting
confidence: 72%
“…The uniaxial pressure increase (up to destruction of the sample) did not change the orientation of the fourth-order axis in (NH 4 ) 3 SiF 7 , similar to that found earlier for (NH 4 ) 3 GeF 7 . 11 Thus, silicon and germanium compounds differ from (NH 4 ) 3 TiF 7 , where small uniaxial pressure reoriented this axis at 90 degrees. 15 Fig.…”
Section: Polarization Opticsmentioning
confidence: 99%
See 3 more Smart Citations